Understanding source–sink interactions: Progress in model plants and translational research to crops - Rosado-Souza, Laise; Yokoyama, Ryo; Sonnewald, Uwe; Fernie, Alisdair R. (Molecular Plant, 2023)
Agriculture is facing a massive increase in demand per hectare as a result of an ever-expanding population and environmental deterioration. While we have learned much about how environmental conditions and diseases impact crop yield, until recently considerably less was known concerning endogenous factors, including within-plant nutrient allocation. In this review, we discuss studies of source–sink interactions covering both fundamental research in model systems under controlled growth conditions and how the findings are being translated to crop plants in the field. In this respect we detail efforts aimed at improving and/or combining C3, C4, and CAM modes of photosynthesis, altering the chloroplastic electron transport chain, modulating photorespiration, adopting bacterial/algal carbon-concentrating mechanisms, and enhancing nitrogen- and water-use efficiencies. Moreover, we discuss how modulating TCA cycle activities and primary metabolism can result in increased rates of photosynthesis and outline the opportunities that evaluating natural variation in photosynthesis may afford. Although source, transport, and sink functions are all covered in this review, we focus on discussing source functions because the majority of research has been conducted in this field. Nevertheless, considerable recent evidence, alongside the evidence from classical studies, demonstrates that both transport and sink functions are also incredibly important determinants of yield. We thus describe recent evidence supporting this notion and suggest that future strategies for yield improvement should focus on combining improvements in each of these steps to approach yield optimization.
CRIS-Team Scopus Importer:2023-01-06
Keywords: assimilate transport; natural variance; nitrogen-use efficiency; photosynthesis; transgenic intervention; water-use efficiency source–sink